The effectiveness of combination of plastic bottle biofilter media and emergent aquatic plant for remediation of rubber industry liquid waste water - Rifka Hendarini Putri; Eko Purwanto; Budijono ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Industrial rubber waste liquid is one of environmental issues that shall be handled as it is commonly discharged and potentially contaminate aquatic environment. This waste contain high organic material and it need to be processed. To understand the effectiveness of combination of plastic bottle biofilter media and emergent aquatic plant for remediation of that waste, a study has been conducted from December 2014 to March 2015. The waste was processed through plastic bottle biofilter media and then flown to phytoremediation unit that was completed with Limmnocharis flava and Echinodorus palaefoliu. The processed waste was then used to rear Cyprinus carpio, Pangasius pangasius and Oreochromis niloticus seeds, 20 fishes/ aquarium (15 L). Water samplings were conducted 3 times, once/ 2 weeks. The water was taken from 5 sampling points, they were in the inlet and in the outlets of the 1st biofilter, 1st phytoremediation, 2nd biofilter and 2ndphytoremediation units. Survival rate of the fish by the end of the research was noted. Results shown that the use of plastic bottle biofilter media and emergent plant phytoremediation process was effective to reduce the organic pollutant. Before being treated, the BOD and COD were 260 mg/L and 400 mg/L respectively. After being treated, the BOD reduced into 28 mg/L and the COD reduced into 60 mg/L. The effectiveness of the processor was 85% for the BOD and 80% for the COD. By the end of the research, survival rate of the fish was ranged from 90% - 100%. Based on data obtained, it can be concluded that the use of plastic bottle and emergent plant is effective for reducing organic materials in rubber industry waste water.Keywords : Plastic bottle, Limmnocharis flava, Echinodorus palaefoliu, Industrial rubber waste liquid